SURG-26. READMISSION FOLLOWING RESECTION FOR PATIENTS WITH BRAIN METASTASES IN THE UNITED STATES. (11th November 2019) - Kotecha, Rupesh; Rubens, Muni; Gonzalez-Arias, Sergio; Siomin, Vitaly; Hall, Matthew; Odia, Yazmin; Vogelbaum, Michael; Mehta, Minesh
Abstract: OBJECTIVE: Up to 30% of cancer patients will develop brain metastasis during the course of their systemic disease with a significant proportion undergoing resection of at least one lesion. The objective of the present study was to characterize the rates, predictors, and costs of 30-day readmissions following craniotomy for brain metastases using a nationally representative database. METHODS: This study was a retrospective analysis of data from the Nationwide Readmissions Database (NRD) from 2010–2014. We included patients who underwent craniotomy for brain metastasis, identified using ICD-9-CM diagnosis (198.3) and procedure (01.59) codes. The primary outcome of the study was unplanned 30-day all-cause readmission rates. Secondary outcomes included predictors and costs of readmissions. RESULTS: During the study period, there were 44, 846 index hospitalizations for patients who underwent resection of brain metastasis. Among this cohort, 17.8% (n=7, 965) had unplanned readmissions within the first 30 days after discharge from the index hospitalization. The readmission rate did not change significantly during the study period ( P =0.286). The odds of unplanned readmission were significantly greater in patients with thromboembolic complications (aOR, 1.53; 95% CI: 1.18–2.01), patients with Elixhauser comorbidities >3 (aOR, 1.35; 95% CI: 1.22–1.50), male patients (adjusted odds ratio [aOR], 1.29; 95% CI: 1.17–1.42), patients with an initial length of stay ≥5 days (aOR, 1.02; 95% CI: 1.01–1.03). The median per-patient cost for 30-day unplanned readmission was 11, 109 and this accounted for a total cost of 132.1 million during the study period. CONCLUSIONS: Unplanned readmissions after resection for brain metastases involve substantial healthcare expenditures. Though there have been many interventions for improving surgical quality, post-operative care, and cost metrics, unplanned readmission rates have not changed. Key patient-specific variables and high rates of comorbidities should be considered to focus our efforts on patient selection for resection, and for strengthening existing interventions for high-risk patients.